Autosuggestion-based Health Innovation RAVS Model for Controlled Blood Pressure in People with Hypertension - Wahidin, W; Raidanti, Dina; Martini, Titin; Oktavia, Ika (Prosiding University Research Colloquium, 2026)
Hypertension is a significant health problem with increasing prevalence globally, nationally, and locally. Adequate blood pressure control is essential to prevent complications. This study develops and evaluates health service innovations based on autosuggestion techniques, using the RAVS Model (Deep Breath Relaxation, Affirmation, Visualisation, and Spirituality) as a holistic approach to blood pressure control in hypertensive patients. A mixed research method, combining bibliometric analysis to map research trends and meta-analysis to assess the effectiveness of RAVS Model interventions from primary studies. The results show that the development of the RAVS model autosuggestion is increasing worldwide, especially in developed countries, and is effective in lowering blood pressure and improving medication adherence. This non-pharmacy innovation offers innovative, accessible, low-cost, and sustainable healthcare solutions. This research makes an essential contribution to developing health services that integrate biological, psychological, social, and spiritual aspects in the management of hypertension.